INTERCONNECTION BETWEEN PERSONALITY SELF-ATTITUDE AND FACTORS INFLUENCING THE CHOICE OF FORMAL AND INFORMAL ADDRESS: PSYCHOLOGICAL AND LINGUISTIC ASPECTS - Berberyan, Asya; Tumasyan, Alina (Modern Psychology, 2023)
The article is dedicated to the study of formal and informal address and factors influencing it from the psychological and linguistic point of view. The purpose of the article is to study and to compare the usage of formal and informal address by the representatives of the Armenian and Russian ethnos from the psychological and linguistic perspectives. The practical part is intended to study the interconnection between these factors and the level of personality self-attitude of the Armenian youth. The studied topic is relevant because it is important for different spheres such as psychology, psycholinguistics, linguistics, and ethics, as formal and informal address is a mean of mutual understanding, interconnection, impact. The subject of the study is formal and informal address in the connection with self-attitude. The used research methods are questioning (authors’ questionnaire) and testing, methodology of self-attitude study by Stolin.
Keywords: formal and informal address; personality self-attitude; psychological and linguistic aspects